2019
DOI: 10.1088/2515-7639/ab4600
|View full text |Cite
|
Sign up to set email alerts
|

Materials selection rules for optimum power factor in two-dimensional thermoelectrics

Abstract: Two-dimensional (2D) materials have emerged as the ideal candidates for many applications, including nanoelectronics, low-power devices, and sensors. Several 2D materials have been shown to possess large Seebeck coefficients, thus making them suitable for thermoelectric (TE) energy conversion. Whether even higher TE power factors can be discovered among the ≈2000 possible 2D materials (Mounet et al 2018 Nat. Nanotechnol. 13 246-52) is an open question. This study aims at formulating selection rules to guide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…This type of band structure can lead to a large Seebeck coefficient and high electrical conductivity, which favors high TE performance. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…This type of band structure can lead to a large Seebeck coefficient and high electrical conductivity, which favors high TE performance. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…A simple model based on effective mass approximation predicts that inelastic scattering in 2D semiconducting materials with step-like DOS can ensure a high power factor. 190 The inelastic processes delay the onset of scattering and maximize the utilization of the Fermi window for transport. The simulations showed that the materials with dominant inelastic processes, specifically when optical phonon energy E ph ∼ 5 k B T , improve the power factor.…”
Section: Recent Strategies To Search For Highly Efficient Te Materialsmentioning
confidence: 99%
“…This combination of features in the DOS, in addition to the secondary bandgap between the lowest and second subbands in TBG, creates a narrow transport distribution function (TDF) [16]. Then states bunched around sharp features in the DOS translate into improved Seebeck coefficient and maximize the PF [17,18]. The highly tunable band structure of TBG offers a new lever of control and a novel avenue to further decouple Seebeck and conductivity to achieve unprecedented PFs.…”
mentioning
confidence: 99%